Impact of indoor environmental quality on students' wellbeing and performance in educational building through life cycle costing perspective - Shan, Xin (2019)
Effects of indoor environmental quality of office buildings on occupants have been widely studied. However, relatively fewer studies focus on that of educational buildings, through the perspective of building life cycle costing assessment in particular. In this study, effects of indoor thermal condition and air quality on students' wellbeing and performance are investigated with other major building metrics through a life cycle costing case study of two university tutorial rooms. Metrics for students' wellbeing and performance are monetized, and different weighting schemes for the metrics are compared with sensitivity analysis. Results show that consideration of students' wellbeing and performance can lead to significant total net benefits, which highlights that other traditional metrics focusing on building energy and resource efficiency should be balanced with human factors. For more sustainable building design and operation, balanced weighting scheme should be adopted, in contrary to the current practice where weights are mainly given to capital and energy while wellbeing and performance are often ignored. The results underscore the importance of incorporating students' wellbeing and performance into educational building design and operation, as thermal or air quality conditions in school classrooms are often worse than stipulations in standards and building codes.